THE ADOLESCENTS' PSYCHOLOGICAL POTENTIAL ACTUALIZATION IN THE TEMPORARY CHILDREN'S ENVIRONMENT CONDITIONS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The using features' opportunities in a temporary children's collective within the children's health and recreation camp recreational and developmental environment for the adolescents' psychological potential actualization are revealed. The author's program concept for the psychological potential's activation, development and actualization is substantiated. Combining the recreational and developmental period of the teenagers' stay in the camp with training classes, accordingly coordinated in terms of goals, tasks, and functions, as well as a person-oriented competence approach to working with children and the transformational interaction concept, led to noticeable changes in behavior already at the first stage.Methods. The comprehensive model for actualizing and developing adolescents' psychological potential was developed during 2017–2020 in the recreational and developmental environment of the "Children's Camp Zephyr" program. The diagnostic toolkit included the hermeneutic method of narrative analysis and a questionnaire with elements of conversation. The model’s development was preceded by a study involving teachers and parents, using the expert method of assessing the effectiveness of learning and motivational activity (subject teachers), and a mixed-type questionnaire to determine motivation, emotional state, physical condition, behavioral manifestations, and values (participants’ parents). During the implementation and adjustment of the program, group test checks were regularly carried out using methods for determining emotional intelligence (N. Hall) and sociometric status.Results. 68 adolescents participated in the study. Specific conditions for actualizing adolescents' psychological potential were identified, and a model of component readiness was developed based on the survey results and analysis of the camp's activities. These features formed the foundation of the model for psychological potential actualization in adolescence.Conclusions. Based on the results of the study and practical work, it can be concluded that using a temporary children's environment is clearly effective for the psychological potential actualization of adolescents when a comprehensive model is applied in a recreational and developmental camp setting.
Keywords: psychological potential; recreational and developmental environment; actualization; emotions, motivation; values; behavior